Familial caregiving perceptions, resources and effects related to family members with DSM-5 mental disorders - Geneta, Kristel Clarence G. (Animo Repository, 2020)
The study seeks to describe the caregiving practices for people with mental health conditions in Metro Manila. Similarities and variations between perception on mental health and access to resources on caregiving experience, and caregiving experience and selfassessed health status are investigated. 15 family caregivers taking care of relatives with mental health conditions were interviewed. These 15 data sets were gathered using in-depth interviews. Positive resource utilization tends to have a positive type of caregiving experience. Positive utilization of resources has more tendencies to experience negative difficulties. More resources mean that family caregivers can make their mental health patients comply with doctor’s orders. Positive utilization of resources has more tendencies to lead to strategies. A positive caregiving experience has a corresponding positive self-assessed health status, and a negative caregiving experience has a corresponding negative health status in the physical and mental domains. Positive caregiving experience shape positive social health while negative caregiving experience shape negative physical and mental self-assessed status.